DEVELOPMENT OF RESEARCH TOOL THROUGH ASSESSING THE KNOWLEDGE AMONG POSTGRADUATES NURSING STUDENTS AT PNS LUMHS - Samina Nawaz Jaat; Husan Bano Channar; Parveen Akhtar; Ali Nawaz Jaat; Abdul Rauf; Rubina Dean (International Journal of Contemporary Issues in Social Sciences, 2024)
Background: One of the main purposes of study was to design a research tool for data collection that enables the researcher to find answers to research questions. Data collection is the process of collecting data aiming to gain insights regarding the research topic. Objectives: To develop a questionnaire to assess the knowledge and practice of MSN students regarding research tools. Methodology: The research study was a cross-sectional. The target population was 33 MSN students from PNS LUMHS, The sampling technique used in the study was the convenient sampling technique. Results: The questionnaire contained 18 items. The Cronbach’s alpha reliability of the questionnaire was α = 0.927. Validity of each item was calculated using SPSS which were also significant. A total of 33 participants were included in the study but majority 60.6% graduates were male. Majority of participants were from 31-35 years of age. Majority 75.8% graduates knew the exact definition of the research tool. 33.3% graduates had conducted research two times. 27.2% knew just one research tool. 93.9% participants who had done research used only questionnaire to collect data. 69.6% had adopted the questionnaire and got permission from the author by mail. While 24.2% had developed questionnaire and checked the reliability and validity by pilot testing. Conclusion: The study was done to develop a questionnaire assessing the knowledge and practice of nursing students regarding research tools development. The development of questionnaire was scientific and reliable.